Propriedades de transporte em barreiras magnéticas em grafeno - Nunes, Edvam de Oliveira (Universidade Federal de São Carlos, 2015)
In this work we studied the properties of Graphene through single and double magnetic barrier. It was used the transfer matrix method for calculating the transmissivity in single and double barriers of monolayer Graphene with magnetic barriers. The transmission was calculated as a function of electron energy for the following conditions: with constant energy, keeping the magnetic fields and varying distances and width of the barriers of the well. For the transmissivity each as function of incidence angle 0, the same procedure was adopted. Situations where the potential V is zero and nonzero were analyzed. Subsequently, we performed calculations of transmissivity for different potentials of zero. The conductance was also calculated as a function of energy, and magnetic field as a function of distance. These calculations were compared using barriers to equal and different magnetic fields. Thus, the transmission probability and the conductance could be modulated by the structural change of the barrier parameters, such as width and height, providing the ability to control electron beams in graphene.
Keywords: Grafeno; Barreiras magnéticas; Transporte; Condutância; CIENCIAS EXATAS E DA TERRA::FISICA